Automated Surface Water Mapping from Resourceat-2 Awifs Image Using Automated algorithm, Krishna District, Andhra Pradesh, India - M. Ganesh, K; Srinivasu, N; N.V.Jagan Mohan, R; Suribabu, G (International Journal of Engineering and Technology, 2018)
In India surface water features are chief source of Irrigation. Irrigation is the application of controlled amounts of water to plants at needed intervals. In the recent past significant investigation has been taken place on surface water features. The surface water includes lakes, ponds, rivers, streams and other exposed inland water bodies. The function of rainfall amounts, intensity of rainfall etc. over season / year are the variation in spatial extent of these features.Â Remote sensing providing lot of data and extracting lot of information over the changes from time to time.Â Nowadays the role of satellite image process is widely used in extraction of water bodies.Â Different researchers are using various methods to delineate water bodies from different satellite imagery varying in characteristics like spatial, spectral, and temporal. Our present study includes an automatic approach to capture the water body from a Resourcesat-2 AWiFS (Advanced Wide-Field Sensor) imagery using a Automated Algorithm for extraction of surface water bodies model. The dynamics of surface water bodies in Study on geospatial analysis of the extraction of water feature sheets for the month of April, 2018 of the study area.Â The water features information was generated on geospatial database from the Resourcesat-2 AWiFS imageÂ By using bands of 1.55- 1.70 Âµm (SWIR), 0.77-0.86 Âµm (NIR), 0.62-0.68 Âµm (Red) and 0.52-0.59 Âµm (Green) for the estimation of the water spread area.Â The Water spread area (WSA) calculated for each is 227428 ha.Â Â